NILAI SOSIAL BUDAYA JEPANG DALAM PERIBAHASA JEPANG YANG MENGGUNAKAN KONSEP BINATANG - Trahutami, Sriwahyu Istana (IZUMI, 2015)
Proverbs conveying animal concepts can be found in almost languages. They are used to express indirectly the speskerâs meaning. The data of the research are taken from Japanese Proverb Dictionary. This study used referential and inferential methods.The methods were used to determine life values in Japanese society or Japanese culture. This analysis reveals that in Japanese proverbs the animal like dog, cat, frog, snake, raccoon, tanuki, fish etc is often mapped on to human beings to expressing human relationship and to show characteristic of the Japanese people and culture.